Maintenance of the running track in stadium of public universities (UiTM, UPM and UKM) / Norhaliza Md Razali - Md Razali, Norhaliza (Faculty of Architecture, Planning and Surveying, 2010)
The maintenance of the running track is mostly important to maintain the investment value of the facilities but it also can reduce the maintenance cost, creates a better image, comfort to all the users and also can lengthen the life span of the running track. The running track have a 6 types, it is are grass track, asphalt-bound track, rubber track, latex-bound track, polyurethane track and synthetic track. Commonly, the synthetic track usually use at the stadium in Malaysia. Every types of the running track have a own construction method and maintenance management. In the process of collecting all the data and information to produce this dissertation report, there are 2 methods of collecting the data from those IPTA which are by interviewing those people who responsible or involves in the maintenance management of the sport facilities provided (staffs of the maintenance department or sport centre) in those IPTA based on the structures interview form made. The second method is from the observation and site visits to identify the condition of the running track at stadium at those 3 IPTA is UiTM, UPM and UKM. According to the interviews carried out with the person who responsible and involves in the maintenance of the running track at every IPTA and the maintenance programmers towards the running track have been identified including the strategy, planning and the procedure of the maintenance work for the running track. Beside that the problem that occur towards the running track can also being identified.